Estudio de la incorporación de CdS y NTsC en una matriz de PMMA como material fotoconductor - Pantoja Castro, Mayra Agustina (Universidad Michoacana de San Nicolás de Hidalgo, 2013)
In this work the addition of cadmium sulfide (CdS) particles and carbon nanotubes (CNTs) to a poly(methyl methacrylate) (PMMA) matrix was analyzed. The resulting material was proposed as potential photoconductor because CNTs and CdS could enhance the electrical current, which result from the conductivity and photoconductivity of CNTs and CdS respectively. A new route of synthesis for PMMA-CdS-CNTs materials was proposed which combines sonochemistry and in-situ polymerization. In the case of CdS, the rapid motion occurring in solution for the sonochemical process inhibits agglomeration and settling of the CdS particles, remaining suspended between the chains of the growing monomer. This route of synthesis favors the dispersion of both CdS and CNTs in the polymer, producing films with CNTs and CdS particles closely spaced in the polymer matrix, and increasing the electrical conductivity of the new material when compared with PMMA-CNTs and PMMA-CdS. Based on FT-IR analysis of PMMA-CNTs materials, a displacement of about 8 cm-1 of the band assigned to carbonyl groups of the polymer relative to the spectrum of pure PMMA was found, this change has been associated with the carbon-carbon bonding and interaction between the polymer and nanotubes resulting from the opening of the ? bonds in the nanotubes. Moreover, impedance tests performed with these materials, allow obtaining a conductivity profile which change from 1x10-14 S-m to 1x10-9 S-m by increasing the concentration of CNTs from 0 to 0.5 wt%. From these results a percolation threshold level was also identified at 0.5 wt% of CNTs, which has been defined as the necessary concentration of dispersed nanotubes in a matrix which are connected or very close to each other, leading to a continuous flow of electrical current.

En este trabajo se analizó la adición de partículas de sulfuro de cadmio (CdS) y nanotubos de carbono (NTsC) a una matriz de poli(metil metacrilato) (PMMA). El material resultante se propuso como potencial fotoconductor debido a que los NTsC y el CdS le pueden impartir a una matriz dieléctrica (PMMA), un aumento en la intensidad de corriente derivada de la conductividad y fotoconductividad de los NTsC y CdS respectivamente. La ruta de síntesis que se propuso en esta tesis para obtener materiales de PMMACdS- NTsC, combina el proceso de sonoquímica y la polimerización in situ. En el caso del CdS, el movimiento rápido que se produce en la solución durante el proceso de sonoquímica, inhibe que el CdS se aglomere y sedimente quedando suspendido entre las cadenas de monómero en crecimiento, favoreciendo la dispersión de estos dos nanocompuestos en el polímero y propiciando que en la película obtenida exista una proximidad entre los NTsC y el CdS, condición que propicio el incremento de la conductividad en este nuevo material comparado con materiales de PMMA-NTsC y PMMA-CdS. A partir de los análisis de FT-IR realizados a materiales de PMMA-NTsC, se encontró un desplazamiento de aproximadamente de 8 cm-1 de la banda de los grupos carbonilos del polímero respecto al espectro del PMMA puro, este cambio ha sido asociado a la unión e interacción carbono-carbono entre el polímero y los nanotubos derivado de la apertura de los enlaces ? en los nanotubos. Por otra parte, las pruebas de impedancia realizadas a estos materiales, permitieron realizar un perfil de conductividad eléctrica donde se observó que ésta pasa de 1x10-14 S-m a 1x10-9 S-m al incrementar la concentración de NTsC de 0 al 0.5% en peso.
Facultad de Ingeniería Química. Doctorado en Ciencias en Ingeniería Química
Keywords: info:eu-repo/classification/cti/7; FIQ-D-2013-2007; PMMA; Nanotubos; Sonoquímica; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/5697